Magnetic Resonance Imaging Diagnosis of Volvulus through Mesenteric Defect in Neonate - Scott Leopold; Mohammed Al-Qaraghouli; Naveed Hussain; Christine Finck (Thieme Medical Publishers, Inc., 2016)
Abstract Antenatal midgut volvulus is a rare surgical emergency in which bowel is severely compromised. Rarely the etiology is a mesenteric defect. Early diagnosis is essential and lifesaving in the immediate newborn period. Typically upper gastrointestinal or ultrasound imaging can be suggestive of the diagnosis of volvulus in the neonate. Sometimes, however, the diagnosis may be elusive. Herein, we report on the use of neonatal magnetic resonance imaging to diagnose a midgut volvulus that occurred through a congenital mesenteric defect.